2012
DOI: 10.1371/journal.pone.0048168
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnicity Differences in HIV-related Stigma Experienced by People Living with HIV in Ontario, Canada

Abstract: This study aimed to understand gender and ethnicity differences in HIV-related stigma experienced by 1026 HIV-positive individuals living in Ontario, Canada that were enrolled in the OHTN Cohort Study. Total and subscale HIV-related stigma scores were measured using the revised HIV-related Stigma Scale. Correlates of total stigma scores were assessed in univariate and multivariate linear regression. Women had significantly higher total and subscale stigma scores than men (total, median = 56.0 vs. 48.0, p<0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
82
8
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 73 publications
(96 reference statements)
19
82
8
4
Order By: Relevance
“…This is inconsistent with studies conducted in Nigeria and Canada, which found that women experience significantly higher levels of HIV-related stigma than men [22,23]. It is proposed that the small number of females in the current sample could have accounted for these findings.…”
Section: Stigma and Gendercontrasting
confidence: 99%
See 2 more Smart Citations
“…This is inconsistent with studies conducted in Nigeria and Canada, which found that women experience significantly higher levels of HIV-related stigma than men [22,23]. It is proposed that the small number of females in the current sample could have accounted for these findings.…”
Section: Stigma and Gendercontrasting
confidence: 99%
“…Additionally, seropositive individuals in Singapore who were more highly educated, reported significantly higher levels of DS. These results show mixed support for previous research, which found that those with more education perceived lower levels of stigma [23,28]. Results obtained for PS are in keeping with previous studies, and suggest that the more highly-educated PLWHA show better understanding of their condition.…”
Section: Stigma and Educational Levelcontrasting
confidence: 44%
See 1 more Smart Citation
“…Algo similar se evidenció para el presente estudio donde la población masculina representa un 83,9% de la población total encuestada, así mismo, un estudio mexicano reportó que el 82.6% de los casos de SIDA en 2008 pertenecían al sexo masculino; lo que concuerda claramente con la población de este estudio (18) . El puntaje general de percepción de estigma de Berger en este estudio fue similar a lo reportado en un estudio realizado en Nigeria (19) donde la media de la escala fue de 99,5 , al igual que un estudio en Canadá (20) donde la escala de Berger abreviada de 20 ítems presentó una media de 49, y un estudio realizado en China (24) donde la media fue de 105,7 en la escala de Berger evidencia que la problemática del estigma en las personas que viven con VIH/SIDA no tiene fronteras, se evidencia en cualquier población y cultura, más en unas que en otras, pero se observa que está presente.…”
Section: Discussionunclassified
“…Besides commercial sex workers, and maybe the traditional high-risk populations of injection drug users, women represent a group with substantial proportion of incident infections. 41,42 Therefore, for the 25% of HIVpositive Canadians who remain unaware of their HIV status, thus continuing to spread HIV to their unsuspecting partners, an offer of self-test may be a potential life saver.…”
Section: Self-testing In the Canadian Contextmentioning
confidence: 99%